2012
DOI: 10.1074/jbc.m112.380139
|View full text |Cite
|
Sign up to set email alerts
|

Monomer-Monomer Interactions Propagate Structural Transitions Necessary for Pore Formation by the Cholesterol-dependent Cytolysins

Abstract: Background:The cholesterol-dependent cytolysins (CDCs) undergo a complex set of structural transitions to form the homo-oligomeric pore complex. Results: Structural transitions are propagated between monomers of the oligomeric complex. Conclusion: Specific structural changes establish the geometry of the oligomeric pore complex and promote the completion of existing oligomers. Significance: CDCs use membrane binding and ordered intermolecular interactions to drive assembly of their ␤-barrel pore.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
72
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(92 citation statements)
references
References 28 publications
20
72
0
Order By: Relevance
“…S5D). Crucially and consistent with this idea, mutagenesis of the equivalent β4-α6 loop structure in CDCs (the β5-region) showed that mobility in this region is essential for initial stable dimer formation as well as subsequent oligomerization events (30,32). Similarly, EM data and mutagenesis data suggest that the equivalent region is also important for assembly of the fungal MACPF protein pleurotolysin (23).…”
Section: Structural Analysis Of the Sntx Dimer In The Context Of A Fusupporting
confidence: 52%
See 1 more Smart Citation
“…S5D). Crucially and consistent with this idea, mutagenesis of the equivalent β4-α6 loop structure in CDCs (the β5-region) showed that mobility in this region is essential for initial stable dimer formation as well as subsequent oligomerization events (30,32). Similarly, EM data and mutagenesis data suggest that the equivalent region is also important for assembly of the fungal MACPF protein pleurotolysin (23).…”
Section: Structural Analysis Of the Sntx Dimer In The Context Of A Fusupporting
confidence: 52%
“…Extensive published experimental data reveal that a key step in prepore assembly is formation of a stable membrane-bound dimer (30). We suggest that the structure of the SNTX heterodimer represents a soluble and stable snapshot of this event.…”
Section: Phylogenetic Analysis Reveals That Sntx Represents An Ancienmentioning
confidence: 99%
“…To determine the relative lytic activities of wildtype PFO and its W165T mutant, a hemolytic assay and fluorometric measurements of carboxyfluorescein release from liposomes were performed. In agreement with previous studies (29), PFO evoked hemolysis of sheep erythrocytes in a dose-dependent manner at 37°C (data not shown). In contrast, the W165T point mutation led to loss of the hemolytic activity even at 100 nM PFO (data not shown).…”
Section: Characterization Of the Binding Of Pfo And Pfosupporting
confidence: 81%
“…Further analysis of the W165T variant indicated that this mutation does not block D4 binding to lipid membrane but disturbs the formation of the ring-shaped oligomeric PFO complex by preventing ␤4 from pairing with ␤1 of another membrane-bound PFO monomer. Instead of ringshaped oligomers, linear oligomers were found in the W165T protein (29). The solution structure of PFO shows that D1 is in direct contact with D2 and D3 domains, which undergo major structural changes during incorporation into the membranes and formation of pores.…”
mentioning
confidence: 99%
See 1 more Smart Citation